New Curriculum to New Pedagogy in Multilingual Context: A journey in Jharkhand - Pattanayak, Binay (Voices of Teachers and Teacher Educators, 2017)
The youngsters of Jharkhand discovered a new educational platform in 2001. This year saw the creation of the new state of Jharkhand, which was formed from Bihar land. In addition to its mineral wealth, the state is regarded as one of the richest in the country due to its vast multicultural and multilingual diversity, which is very beneficial for kids' education. But the state had trouble establishing a stable government until 2014. In addition to being governed by the Center three times, it saw more than ten governments, ten chief secretaries, and an equivalent number of chief justices. Continuous political and administrative instability, civil unrest, a lack of educational professionals in the system, inadequate infrastructure, corruption, and a number of other social problems that impacted children's lives throughout the state all had a negative impact on educational activities in the state. The state has not yet established a fully functional SCERT as of yet.